Penerapan Strategi Pembelajaran Project Based Learning untuk Mengurangi Penggunaan Gadget Berlebihan dalam Pembelajaran pada Siswa Kelas XI SMA Negeri 13 Gowa - Muhammad Sarfito Patto; Fatiama Fatiama; Lukman Ismail (Badan Penerbit STIEPARI Press, 2025)
This classroom action research aimed to reduce excessive gadget use that disrupts concentration and learning outcomes among 11th-grade students at SMA Negeri 13 Gowa through the implementation of Project-Based Learning (PjBL). Conducted from February 4 to April 30, 2025, the study employed a classroom action research method, encompassing planning, implementation, observation, and reflection. The subjects were 30 11th-grade students, with data collected via observation, interviews, and quantitative analysis. Results showed a reduction in irrelevant gadget use by 60% in cycle I and 80% in cycle II, alongside an increase in student engagement from 40% to 60%. PjBL effectively enhanced social interaction and learning motivation. This study demonstrates that active learning strategies can shift students’ focus from gadgets to meaningful learning activities.